Magnetic resonance imaging in the diagnosis and follow up of Takayasu's arteritis in children. Issue 6 (1st June 2002) - Aluquin, V P R; Albano, S A; Chan, F; Sandborg, C; Pitlick, P T
Abstract : Background: Takayasu's arteritis (TA) has a mortality rate of up to 40% in children. Because the clinical presentation of TA is often non-specific, accurate and prompt diagnosis depends on a high degree of awareness and appropriate laboratory and imaging studies. Objective: To examine the use of advanced magnetic resonance imaging (MRI) in evaluating, gauging activity, and following the complications of TA. Methods and results: T1 weighted, T2 weighted, contrast enhanced MR images, and MR angiograms of the chest and abdomen were obtained in three children (age range 11–14 years). The MRI studies confirmed the diagnosis of active TA and were repeated to evaluate response to treatment. Two patients showed complete resolution of lesions found on MRI at six and 12 months' follow up, while the third patient showed no significant improvement. Conclusion: MRI can be used to help establish the initial diagnosis of TA in children, and it can also be used to monitor disease activity and to guide treatment.